DISEASE PROBlEMS IN SHRIMP SECTOR IN KHUlNA DISTRICT OF BANGlADESH: A QUESTION OF SUSTAINABIUTY
Disease is the main restraining factor for the development of shrimp sector in Bangladesh. Both brackish water shrimp bagda (Penaeus monodon